Gender Equality and Social Inclusion Policies: Considerations in Health Sectors in Nepal - Dulal, Tulasa Devi (Patan Pragya, 2023)
This article tries to highlight the existing gender equality and social inclusion GESI policies and practices in health sectors in Nepal. Nepal has participated and ratified the gender policies in all Conventions and Conferences. To fulfill this very obligation, it has introduced some legal provisions and made an attempt to implement them. Due to this region, Nepal has started to address the gender issues in health sectors from Interim Constitution 2007AD addresses health as a fundamental right and that have very citizen shall have the right to basic health services free of cost from the state, as provided in law. Ninth, Tenth and Three-Year Interim Plan have pursued gender equality and women’s empowerment through a gender mainstreaming strategy. The governance framework, fundamental rights and directives of the constitution provide the impetus for revising the 2009 Gender Equality and Social Inclusion (GESI) Strategy of the Health Sector and to align the strategy with the new governance arrangements and state obligations. The institutional structure to lead and coordinate the mainstreaming of GESI into the health system was created in 2012. The Health Sector Gender Equality and Social Inclusion Strategy (2010) provides the foundation for mainstreaming GESI, ensuring that policy development and programme planning are viewed through a create a favourable environment for the use of rights based approaches and more equitable access to healthcare. Implementation of the strategy is guided by the GESI Operational Guidelines (2013). Constitution of Nepal 2015 AD has also considered the rights of women as the right to receive special opportunities based on positive discrimination in education, health, employment, and social security. The Sustainable Development Goals by 2030 and the Nepal Health Sector Strategy (2015-2020) embrace the importance of gender equality, and leaving no one behind to achieve health goals.